Examining the Impacts of Celebrity Endorsement on Consumer Buying Behavior: A Gender-Based Perspective - Dr. Ali Muhammad Mohmand; Gulmakai Mohmand (Journal of Business & Tourism, 2021)
To sustain competitive advantage in consumer markets, companies often use celebrity endorsement as a promising strategy for brands‟ promotion. Several studies have investigated the impact of celebrity endorsement on consumers‟ buying behavior. Nevertheless, little research is conducted to relate celebrity endorsement to purchase intention with a differentiated perspective on males and females apart. This study therefore examines the effects of celebrity endorsement on consumers‟ buying behavior by empiricising sourcecredibility model encompassing good looks, trustworthiness, attractiveness and expertise. Data were collected by a mix of intercept and online surveys undertaken from undergraduate students in the two capital cities i.e. Islamabad (national capital) and Peshawar (provincial capital). A total number of 172 usable questionnaire responses were received for analysis. Respondents were asked to rate the effects of 10 celebrities mostly in the fashion industry. Descriptive statistics are presented first to present sample profile. Comparative results find that consumers‟ buying behavior was highly affected by celebrity endorsers‟ expertise and trustworthiness. Also, male and female buying behavior wasdeemed similar under the effects of attractiveness, trustworthiness and expertise of celebrity endorsers. However, females had very different perceptions about the importance of „good looks‟ and celebrity endorsements than male counterparts. Finally, when asked about rating favorite celebrities, male and female gave higher weightage to Shaan and Ahsan khan, consecutively. Surprisingly, ShahidAfridi was ranked 6th in terms of source credibility. Overall, celebrity endorsement proves to be an effective strategy to grab consumers‟ attention but it bears little impact on actual consumers‟ buying as several other factors like price and quality are at foreplay. The study bears widespread implications for Marketing researchers and companies to focus on bringing the right celebrity for promoting the right products carrying differentiated gender perspective.